Editorial - Sotiriou, Sofoklis (Open Schools Journal for Open Science, 2026)
In the first issue of 2026, our student scientific journal travels - from the familiar excitement of holiday storytelling to the frontiers of astronomy, quantum science, and the deep ocean - showing how curiosity becomes knowledge when it is paired with method, evidence, and clear thinking. Across the ten contributions that form the issue, a shared message emerges: Scientific progress - whether in “magical” logistics, astronomy in schools, quantum technologies, or ocean sustainability - depends on the same foundations: curiosity guided by structure, imagination tested by evidence, and knowledge communicated with care. We congratulate all student authors for their work and invite readers to approach each article with the same spirit that created it: open-minded, critical, and ready to ask the next question.